Insight into occupancy determinants and conflict dynamics of grey wolf (Canis lupus) in the dry temperate zone of Hindukush Range - Ejaz Ur, Rehman (2021)
The grey wolf (Canis lupus) is a widespread but locally endangered species across Pakistan. The current study investigates the occupancy of grey wolf and conflict with humans in Khanbari Valley Gilgit Baltistan. The study was conducted from the 5th of December 2014 to the 11th of January 2015. The study area was delineated into blocks following natural watersheds, and overall 47 motion-triggered cameras were installed in various locations encompassing an area of 810 km2 with an effort of 1428 trap nights. A human-wolf conflict survey was carried out through questionnaires, where 57 respondents were randomly chosen from 08 villages in the valley. Grey wolf was photo-captured at 11 different camera stations, occupancy estimated at 0.37 ± 0.22 S.E., and detection probability of 0.29 ± 0.19 S.E was obtained. A total of 166 livestock were killed which incurred an economic loss of USD 17,046 (USD 299 per household) in five years. Predation on goat was highest, though consumed as per availability. Sheep predation indicates selection for this animal because predation was much higher than availability. Cattle was predated as per availability and accounts for the least part of the livestock loss. Predation of livestock was greatly influenced by four factors: habitat, prey type, prey age, and time of predation. We recommend conservation initiatives like compensation for economic losses, construction of predator-proof corrals, and awareness campaigns to promote human-wolf co-existence in the area.